O ensino de matemática aliado à educação financeira - Gonçalves, Domingos Sávio de Sousa (2015)
Due to little interest from students in Mathematics came to me the concern of research on the Financial Education theme inserted with the mathematics content. Parti the hypothesis that financial education could give more meaning discipline of mathematics and also educate students financially, thus causing a benefit of society in general. To better understand the topics surveyed attended lectures and watched studies of some authors that speak of teaching / learning, Mathematics and Education Financial Education as ESTEBAN, MACHADO, ROBERTS, SCHENEIDER and others. Investigated two classes where mathematics classes minister of 1 and 2 years of high school, hoping to find answers to some questions that guided me in the progress of the work: What is the interest of students as Financial Education? The financial education can contribute to the teaching of Mathematics? What financial issues are most popular with students? What mathematical content that can be worked with the Financial Education? What level of knowledge by the students of some financial concepts? Have a difference in teaching / learning to solve with the students issues and prepared,involving Finance and Mathematics, rather than the teaching / learning conventional? What contributions this work can bring to society in general? To search for answers to the above questions, I used some qualitative and quantitative instruments, questionnaires compounds and mathematical and financial issues built by me and which were carried out with 51 high school students. The survey revealed that students are deficient in financial language (language that they usually come in national tests, accesses the vestibular and contests), who long enough to increase their financial knowledge that when making financial environment issues provide much attention to mathematical content embedded in these issues. It also showed that, with a little creativity the teaching part, you can work several mathematical content along with financial matters, including geometry. The survey revealed that even those students who say they do not like mathematics discipline are willing and risk making calculations and reason more for being working with financial issues that interest them because they realize that such things do and will take part in their daily lives in the present and future. The main purposes of this study were: 1) to produce an article education which would help mathematics teachers to have greater attention from students in their discipline; 2) to make the students realize how Mathematics is part of their daily lives, even complex contents have their applicability; 3) give definitions and financial concepts that help students in solving problems and in their lives.